The rise of an African middle class : colonial Zimbabwe, 1898-1965 - West, Michael O. (Michael Oliver) (Indiana University Press, 2002)
Tracing their quest for social recognition from the time of Cecil Rhodes to Rhodesia's unilateral declaration of independence, Michael O. West shows how some Africans were able to avail themselves of scarce educational and social opportunities in order to achieve some degree of upward mobility in a society that was hostile to their ambitions. Though relatively few in number and not rich by colonial standards, this comparatively better class of Africans challenged individual and social barriers imposed by colonialism to become the locus of protest against European domination.
Keywords: Middle class -- Zimbabwe -- History.; Zimbabwe -- Colonial influence.; Zimbabwe -- Politics and government -- 1890-1965.; Classes moyennes -- Zimbabwe -- Histoire.; Zimbabwe -- Influence coloniale.; Zimbabwe -- Politique et gouvernement -- 1890-1965.; 15.80 history of Africa.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; SOCIAL SCIENCE -- Anthropology -- Cultural.; Colonial influence; Middle class; Politics and government; Zimbabwe; Mittelstand; Simbabwe; Middenklassen.; Kolonialisme.; 1890-1965; History